2017
DOI: 10.18632/oncotarget.16815
|View full text |Cite
|
Sign up to set email alerts
|

Serrated adenocarcinoma morphology in colorectal mucinous adenocarcinoma is associated with improved patient survival

Abstract: Colorectal mucinous adenocarcinoma (MAC) and serrated adenocarcinoma (SAC) share many characteristics, including right-side colon location, frequent mucin production, and various molecular features. This study examined the frequency of SAC morphology in MACs. We assessed the correlation of SAC morphology with clinicopathological parameters, molecular characteristics, and patient prognosis. Eighty-eight colorectal MACs were collected and reviewed for SAC morphology according to Makinen's criteria. We sequenced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
1
7
0
1
Order By: Relevance
“…Also, distinguishing between colon and rectal cancer may also be important in future studies, since results from rectal cancer (in particular for stage IV patients) differed significantly from colon cancer and (in univariate analysis) influenced the overall results of survival analyses of these patients. Finally, serrated adenocarcinoma morphology in colorectal MAC was recently published to exhibit a significantly higher relapse-free survival compared to non-serrated adenocarcinoma MAC CRC ( p = 0.035, [20]). It remains to be seen if this translates into diverse clinical decision pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Also, distinguishing between colon and rectal cancer may also be important in future studies, since results from rectal cancer (in particular for stage IV patients) differed significantly from colon cancer and (in univariate analysis) influenced the overall results of survival analyses of these patients. Finally, serrated adenocarcinoma morphology in colorectal MAC was recently published to exhibit a significantly higher relapse-free survival compared to non-serrated adenocarcinoma MAC CRC ( p = 0.035, [20]). It remains to be seen if this translates into diverse clinical decision pathways.…”
Section: Discussionmentioning
confidence: 99%
“…results from malignant transformation of serrated polyps, such as SSA and TSA, through the serrated pathway. 11,12 This type of carcinoma was first introduced by Jass et al 13 followed by the proposed morphological criteria of Tuppurainen et al 8 and was finally recognized by the WHO as colon adenocarcinoma in 2010. 2 About 7.7% and 2.1% of cases were diagnosed as unequivocal and equivocal SA among all CRC cases, respectively.…”
Section: Samentioning
confidence: 99%
“…This is characterized by CpG island hypermethylation in the promoter regions of carcinogenesis-related genes, resulting in epigenetic silencing. [8] Milewski et al found that the transcription factor Forkhead box M1 (FOXM1) is an essential gene for the progression of lung cancer to MAC. Inhibition of either FOXM1 or anterior gradient 2 (AGR2) in human pulmonary invasive MAC inhibited mucinous characteristics, [18] Thus, MAC seems to be the result of further development of adenocarcinoma, and the process can be regulated by certain genes such as FOXM1.…”
Section: Discussionmentioning
confidence: 99%